2019
DOI: 10.1187/cbe.18-07-0110
|View full text |Cite
|
Sign up to set email alerts
|

Introductory Biology in Social Context: The Effects of an Issues-Based Laboratory Course on Biology Student Motivation

Abstract: We investigated the effects of a laboratory curriculum developed using the socio-­scientific issues (SSI) framework to contextualize scientific and socially relevant issues for students. Using self-determination theory and hierarchical linear modeling, we examined the effects of the SSI curriculum relative to a control curriculum on student motivation in a large introductory biology course for life science majors. The SSI group had a significant increase in motivation for engaging in the laboratory work relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
2
26
0
2
Order By: Relevance
“…SDT states that the more a person's psychological needs are met, the more internally motivated they will be in that particular situation (27). Research on different aspects of biology education has shown that SDT can explain the positive effects of teambased learning (28), socio scientific issues-based laboratory curricula (29), mentoring interventions (30), and STEM retention resulting from scalable STEM academy programs (31,32).…”
Section: Sdt and Fostering Student Successmentioning
confidence: 99%
“…SDT states that the more a person's psychological needs are met, the more internally motivated they will be in that particular situation (27). Research on different aspects of biology education has shown that SDT can explain the positive effects of teambased learning (28), socio scientific issues-based laboratory curricula (29), mentoring interventions (30), and STEM retention resulting from scalable STEM academy programs (31,32).…”
Section: Sdt and Fostering Student Successmentioning
confidence: 99%
“…Finally, thematic courses, case studies, and thematic assignments can be used to integrate social justice issues into traditional biology courses. The addition of social justice issues into the STEM curriculum allows students to explore concepts from a variety of perspectives and viewpoints ( 35 ), contextualize material, and enhance their motivation by establishing increased feelings of relatedness ( 36 , 37 ). Most notably, a thematic approach may increase retention of students from underrepresented groups in STEM courses and encourage underrepresented minorities to pursue STEM pathways ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior DBL and PBL research offer evidence that providing a socio-scientific rationale for course tasks supports gains in students' conceptual understanding and knowledge building (Hewitt et al 2019;Venville and Dawson 2012;Udovic et al 2002). Further, engaging in a project supports students' ability to apply their knowledge (Bransford et al 1989;Dochy et al 2003;Gijbels et al 2005;Strobel and Van Barneveld 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Students achieve higher content gains than students not learning through a socio-scientific lens in these cases (e.g. Benware and Deci 1984;Hewitt et al 2019;Venville and Dawson 2010). However, other research indicates that students in classes incorporating applied learning and/or socio-scientific issues have either equal or negative content gains relative to students who learn without incorporation of these issues (Dochy et al 2003;Eastwood et al 2013;Sadler and Dawson 2012).…”
Section: Applied Learning's Influence On Content Knowledgementioning
confidence: 98%
See 1 more Smart Citation